Individual and Collective Responsiveness to Climate Change: A Response to Dwyer - Macpherson, Cheryl (BioéthiqueOnline)

(untitled) (BioéthiqueOnline, 2016)
James Dwyer’s story about a fictional GAIA Commission highlighted unresolved concerns about the scope of bioethics, specifically regarding the global distribution of, and responsibility for, the health impacts of climate change. This commentary discusses the potential impact of an individual on greenhouse gas emissions and the importance of engaging institutional responses in order to have meaningful impacts.